Vestibular paroxysmia associated with congenital vascular malformation: A case report - Liu, Fei; Zhang, Zheng; Wei, Wan; Jiang, Lin (Frontiers in Neuroscience, 2023)
Vestibular paroxysmia (VP) is an uncommon paroxysmal disease, characterized by vertigo, tinnitus, and postural unsteadiness. The main reason of VP is neurovascular cross compression, while few cases of VP accompanied with congenital vascular malformation were reported. Here, we describe a 22-year-old patient with VP caused by congenital anterior inferior cerebellar artery (AICA) malformation who completely recovered after taking oral medicine. This report shows that VP caused by congenital vascular malformation can occur in adults and that oral medication is effective.